2017
DOI: 10.1016/j.jcrc.2016.09.011
|View full text |Cite
|
Sign up to set email alerts
|

Hematologic counts as predictors of delayed cerebral ischemia after aneurysmal subarachnoid hemorrhage

Abstract: Introduction Aneurysmal subarachnoid hemorrhage (SAH) is associated with high morbidity and mortality, and ischemic lesion burden is a known predictor of worse outcome. Currently, there is no single clinical method or ancillary test that can reliably predict which subset of patients will develop delayed cerebral ischemia (DCI). Previous animal and human studies suggest that SAH leads to a state of systemic inflammation, with DCI as the most striking manifestation. The aim of this study was to find hematologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…This study builds upon results from prior studies, which have demonstrated the role of peripheral leukocytes after SAH. While several important studies have shown that WBC count has an association with DCI ( 62 , 63 ), herein we have provided a comprehensive assessment of the role of differential cell counts on DCI and functional outcomes. Our assessments of the role of sex differences and associations with infection have also not been addressed in prior studies.…”
Section: Discussionmentioning
confidence: 99%
“…This study builds upon results from prior studies, which have demonstrated the role of peripheral leukocytes after SAH. While several important studies have shown that WBC count has an association with DCI ( 62 , 63 ), herein we have provided a comprehensive assessment of the role of differential cell counts on DCI and functional outcomes. Our assessments of the role of sex differences and associations with infection have also not been addressed in prior studies.…”
Section: Discussionmentioning
confidence: 99%
“…Delayed cerebral ischemia is one of the major complications of aSAH and one of the leading causes of high morbidity and mortality. Early diagnosis and management of vasospasm following aSAH is an important step to improve the prognosis [9] . The aim of this work was to assess the value of EEG monitoring and TCD as early biomarkers of vasospasm following aSAH and the value of early intervention to avoid the consequences of DCI.…”
Section: Discussionmentioning
confidence: 99%
“…McGirt et al 134 224 cases, Retrospective 1-5 days post SAH Serum leukocyte count greater than 15 Â 10 9 /L was independently associated with vasospasm. Da Silva et al 220 55 cases, Retrospective 32 30 cases, Prospective 6 h -7 days after IS onset Neutrophil count was negatively associated with spleen volume change. Leukocyte count did not predict outcome.…”
Section: Peripheral Immune Cells and Hemorrhagic Strokementioning
confidence: 97%